Tarqiyat Natā’ij Ta‘allum al-Lughah al-‘Arabīyah bi-Istikhdām Uslūb al-Thawāb wa-al-‘Iqāb - Muhammad Kamal Bin Abdul Hakim; Chakam Failasuf; Lulu Mauliadana (Al-Ma‘rifah, 2021)
This study aims to determine the improvement of Arabic learning outcomes using rewards and punishments. The research used an action research method by Kemmis and McTaggart model and was carried out in two cycles. The research subjects were grade 7 students of SMP Muhammadiyah 3 Jakarta, totaling 36 students including 19 male students and 17 female students. The instruments used tested learning outcomes and observation sheets. Learning outcome tests are used to measure the success of students in understanding Arabic lessons. Meanwhile, the observation sheet is used to measure the performance of teachers and students in learning. The scores that have been achieved by the students during the study are the pre-cycle score is 65,83, the exam score for cycle 1 is 66,80, and the exam score for cycle 2 is 75,69. There was an increase in the value from the pretest to the test cycle 1, namely 0,99, and the increase from cycle 1 to cycle 2 is 8,89. The number of improvement results in this study was 9,88. By using reward and punishment, students are more active in learning and can relate the subject matter to the surrounding environment and practice it directly in the classroom.